Comparative Analysis of the Complete Chloroplast Genome of Four Endangered Herbals of Notopterygium - Yang, Jiao (Genes (Basel), 2017)
Notopterygium H. de Boissieu (Apiaceae) is an endangered perennial herb endemic to China. A good knowledge of phylogenetic evolution and population genomics is conducive to the establishment of effective management and conservation strategies of the genus Notopterygium. In this study, the complete chloroplast (cp) genomes of four Notopterygium species (N. incisum C. C. Ting ex H. T. Chang, N. oviforme R. H. Shan, N. franchetii H. de Boissieu and N. forrestii H. Wolff) were assembled and characterized using next-generation sequencing. We investigated the gene organization, order, size and repeat sequences of the cp genome and constructed the phylogenetic relationships of Notopterygium species based on the chloroplast DNA and nuclear internal transcribed spacer (ITS) sequences. Comparative analysis of plastid genome showed that the cp DNA are the standard double-stranded molecule, ranging from 157,462 bp (N. oviforme) to 159,607 bp (N. forrestii) in length. The circular DNA each contained a large single-copy (LSC) region, a small single-copy (SSC) region, and a pair of inverted repeats (IRs). The cp DNA of four species contained 85 protein-coding genes, 37 transfer RNA (tRNA) genes and 8 ribosomal RNA (rRNA) genes, respectively. We determined the marked conservation of gene content and sequence evolutionary rate in the cp genome of four Notopterygium species. Three genes (psaI, psbI and rpoA) were possibly under positive selection among the four sampled species. Phylogenetic analysis showed that four Notopterygium species formed a monophyletic clade with high bootstrap support. However, the inconsistent interspecific relationships with the genus Notopterygium were identified between the cp DNA and ITS markers. The incomplete lineage sorting, convergence evolution or hybridization, gene infiltration and different sampling strategies among species may have caused the incongruence between the nuclear and cp DNA relationships. The present results suggested that Notopterygium species may have experienced a complex evolutionary history and speciation process.